ALLOWANCE FOR SETUP TIME UNDER STANDARD COSTS. - Andersson, Henry F. (The Accounting Review, 1960)
The paper explains the development of formula, based upon historical costs, for computing the setup time. By accounting for setup time in the costing of various parts, a more realistic price for the product may be established. In the evolution of the formula, a basic assumption is made that unit machining time for a part, excluding setup time, remains constant and that the variations are explained by divisions of the setup time for smaller and for larger quantities of parts manufactured. Under present day cost procedures, standard variations are adequately accounted for, so that steps may be taken to improve the company's manufacturing efficiency. However, when the objective of a cost system becomes not only a means of calling the management's attention to variations from standards set for material, labor, and indirect expenses, but also a tool for pricing special repair parts, such formulas are derived to interpret and evaluate the costs. This formula, developed to establish standard costs based on various quantities of production, gives the accountant a most useful tool in analyzing costs.